Haemaphysalis hystricis Supino 1897 ... - Petney, Trevor N.; Boulanger, Nathalie; Saijuntha, Weerachai; Chitimia-Dobler, Lidia; Pfeffer, Martin; Eamudomkarn, Chatanun; Andrews, Ross H.; Ahamad, Mariana; Putthasorn, Noppadon; Muders, Senta V.; Petney, David A.; Robbins, Richard G. (Zenodo, 2019)
Haemaphysalis hystricis Supino, 1897 Haemaphysalis hystricis is a forest-dwelling species that has been found in Indonesia (the islands Sulawesi and Sumatra), Lao PDR, Myanmar, peninsular Malaysia, Thailand and Vietnam, as well as in China, Hong Kong, northwest India, Sri Lanka, Taiwan and the Ryukyu Islands (Hoogstraal et al. 1965c; Tanskul and Inlao 1989; Geevarghese and Mishra 2011; Ernieenor et al. 2017). It occurs from low altitudes to over 2,000 m above sea level (Hoogstraal et al. 1965c). Adults are known to attack humans, dogs, and a variety of medium- to large-sized wild mammals, including boar, deer, and tiger (Hoogstraal et al. 1965b; Tanskul and Inlao 1989; Grassman et al. 2004). Limited collections are also known from buffalo and a large scimitar babbler (Pomatorhinus hypoleucos). Nymphs have been collected from humans, Asian palm civet (Paradoxurus hermaphroditus), ferret-badger, squirrels and the black rat, Rattus rattus, and both larvae and nymphs have been collected from barking deer and ... : Published as part of Petney, Trevor N., Boulanger, Nathalie, Saijuntha, Weerachai, Chitimia-Dobler, Lidia, Pfeffer, Martin, Eamudomkarn, Chatanun, Andrews, Ross H., Ahamad, Mariana, Putthasorn, Noppadon, Muders, Senta V., Petney, David A. & Robbins, Richard G., 2019, Ticks (Argasidae, Ixodidae) and tick-borne diseases of continental Southeast Asia, pp. 1-89 in Zootaxa 4558 (1) on page 26, DOI: 10.11646/zootaxa.4558.1.1, http://zenodo.org/record/2613120 ...